Modeling the Influence of the Penetration Channel’s Shape on Plasma Parameters When Handling Highly Concentrated Energy Sources - Dmitriy N. Trushnikov; Ekaterina S. Salomatova; Igor I. Bezukladnikov; Igor L. Sinani; K. P. Karunakaran (Advances in Materials Science and Engineering)
In our work to formulate a scientific justification for process control methods when processing materials using concentrated energy sources, we develop a model that can calculate plasma parameters and the magnitude of the secondary waveform of a current from a non-self-sustained discharge in plasma as a function of the geometry of the penetration channel, thermal fields, and the beam’s position within the penetration channel. We present the method and a numeric implementation whose first stage involves the use of a two-dimensional model to calculate the statistical probability of the secondary electrons’ passage through the penetration channel as a function of the interaction zone’s depth. Then, the discovered relationship is used to numerically calculate how the secondary current changes as a distributed beam moves along a three-dimensional penetration channel. We demonstrate that during oscillating electron beam welding the waveform has the greatest magnitude during interaction with the upper areas of the penetration channel and diminishes with increasing penetration channel depth in a way that depends on the penetration channel’s shape. When the surface of the penetration channel is approximated with a Gaussian function, the waveform decreases nearly exponentially.